Characterisation of diesel particulate emission from engines using commercial diesel and biofuels. (June 2016) - Ajtai, T.; Pintér, M.; Utry, N.; Kiss-Albert, G.; Gulyás, G.; Pusztai, P.; Puskás, R.; Bereczky, Á.; Szabados, Gy.; Szabó, G.; Kónya, Z.; Bozóki, Z.
Abstract: In this paper, the number concentration and the size distribution of diluted diesel exhaust particulate matter were measured at three different engine operating points in the speed-load range of the engine as follows: 1600 rpm; 50% load, 1900 rpm; 25% load, 1900 rpm; 75% load, adopted from the UN ECE Vehicle Regulation no. 49 (Revision 2) test protocol using pure diesel and biodiesel fuels, as well as their controlled blends. The emitted particulate assembly had lognormal size distribution in the accumulation mode regardless of the engine operational condition and the type of fuel. The total number and volume concentration emitted by the diesel engine decreased with increasing revolution per minute and rated torque in case of all the fuel types. The mixing ratio of the fuels did not linearly affect the total emission but had a minimum at 75% biodiesel content. We also studied the thermal evolution of the emitted particulates using a specially designed thermodenuder (TD) heated at specific temperatures (50 °C, 120 °C, and 250 °C). The first transition, when the temperature was increased from 50 °C to 120 °C resulted in lower number concentrations with small relative shifts of the peak position. However, in case of the second transition, when the temperature reached 250 °C the individual volatile particulates adsorbed onto the surface of soot particles were completely or partly vaporised resulting in lower total number concentrations with a substantial shift in peak position. Highlights: We investigated the diluted exhaust emitted by a diesel engine. The engine was operated with various mixtures of diesel and biodiesel fuels. Concentration and size distribution strongly depend on engine condition and fuel type. The thermal evolution of the emitted particulates was also investigated. Changes in concentration and structure were both observed due to thermal treatment.